Affective Commitment as a Mediator in Enhancing Logistics Service Quality - Sitanggang, Rohana D.M.; Saribanon, Euis; Setiawati, Aswanti; Wahyuni, Rr. Endang; Thabah, Asep Ali (Jurnal Minds: Manajemen Ide dan Inspirasi, 2024)
This study examines the effects of organizational culture, job satisfaction, and servant leadership on service quality, with affective commitment as a mediating mechanism, in freight forwarding companies in Jakarta, Indonesia. Its novel contribution lies in identifying affective commitment as the primary psychological conduit through which job satisfaction influences service quality, while revealing uneven mediation effects across cultural and leadership factors in a logistics setting. A quantitative design was applied using data from 262 respondents selected through purposive sampling. Primary data were collected via online questionnaires and analyzed using SEM-PLS. The findings show that affective commitment fully mediates the job satisfaction–service quality relationship and partially mediates the effects of organizational culture and servant leadership. Job satisfaction has no direct effect on service quality. The results imply that compensation, promotion, and leadership practices must prioritize affective commitment to achieve sustained service quality improvements.